Administrasi dan Manajemen Pendidikan Islam - Radjaming, Nawir (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2025)
Educational Administration or a process of overall activities working together in the field of Education that includes planning, organizing, directing, reporting, coordinating, supervising, and financing by using or utilizing available facilities both personnel, materials, and spiritual to achieve educational goals effectively and efficiently. There are several factors that drive the emergence of administration, including: (1) The significant changes in Educational Institutions from small products or small schools with a single teacher to a school (madrasah) that includes a large number of teachers wanting the establishment of a principal or director who is administratively responsible. (2) The expansion of education and the implementation of compulsory education requiring the preparation of students, teachers, and resources for the teaching and learning process. (3) Changes and necessary developments in the nature of teaching, its objectives, and functions, which are no longer about rote memorization aimed at teaching and acquiring limited knowledge and limited methods that only apply in the classroom, but teaching that has changed in nature, goals, and functions. Educational Administration is the entire process of directing and integrating everything, both personal, spiritual, and material, related to achieving the the achievement of educational goals. The general objectives of educational administration in Islamic education are: (1) To facilitate administrative and educational work, making processes easier, (2) To create a spiritual, psychological, and social environment that is implemented according to Islamic faith and morals full of faith and honesty. (3) To enhance the morale or spirit of the members of educational institutions and develop camaraderie among them. (4) To increase the productivity of workers in administrative apparatus or educational institutions, improving quality, methods, and media. (5) To develop a continuous administrative system and media and improve the skills of workers in institutions while continuously enhancing their knowledge, skills, and attitudes. (6) To bring about desired changes in the educational process in all its aspects and help students achieve comprehensive and holistic growth. (7) To connect the educational process with the goals of community development and strengthening the relationship of Educational Institutions with their environment.